2004
DOI: 10.1002/j.1939-4640.2004.tb02813.x
|View full text |Cite
|
Sign up to set email alerts
|

The 25th Volume: Role of the GATA Family of Transcription Factors in Andrology

Abstract: Understanding how genes get turned on or off is central to the study of biological processes in both health and disease. Several regulatory mechanisms, which can be positive or negative, have been implicated in the control of tissue-and cell-specific gene expression. These include modulation of chromatin structure, DNA methylation, and the regulation of transcription and translation. Transcription factors are nuclear regulatory proteins that bind specific DNA sequences in the 5Ј regulatory or promoter regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 131 publications
2
37
0
Order By: Relevance
“…These are highly conserved zinc finger-containing proteins that are found across the phylogenetic scale where they have conserved roles regulating cell differentiation, organ morphogenesis, and tissue-specific gene expression (32,34,61,62,68). In the reproductive system, GATA4 is essential for mouse gonad development and male sex determination (34,62). While the precise mechanism by which GATA4 drives the indifferent gonad down the male pathway remains to be determined, various GATA4-regulated genes have been identified that are likely to have a role, including the male-determining gene Sry and the male-inhibitory gene Mis (60).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These are highly conserved zinc finger-containing proteins that are found across the phylogenetic scale where they have conserved roles regulating cell differentiation, organ morphogenesis, and tissue-specific gene expression (32,34,61,62,68). In the reproductive system, GATA4 is essential for mouse gonad development and male sex determination (34,62). While the precise mechanism by which GATA4 drives the indifferent gonad down the male pathway remains to be determined, various GATA4-regulated genes have been identified that are likely to have a role, including the male-determining gene Sry and the male-inhibitory gene Mis (60).…”
Section: Discussionmentioning
confidence: 99%
“…To test this prediction, we used real-time RT-PCR analysis to examine GATA transcription factor mRNA levels. Sertoli cells are known to express GATA4 and GATA6 (62), and thus we predicted that one or both of these factors would be lower in 15P1 and TM4 cells than in MSC1 cells. Indeed, we found that Gata4 and Gata6 transcripts were expressed at lower levels in 15P1 and TM4 cells than in MSC1 cells (Fig.…”
Section: Identification Of Ares Essential For Rhox5 Pp Transcription mentioning
confidence: 99%
See 2 more Smart Citations
“…FOG2 is a multitype zinc finger cofactor that binds to and regulates the transcriptional activity of GATA4, a member of the GATA family of transcription factors (22)(23)(24). In mice, Fog2 and Gata4 are coexpressed in the somatic cells of XX and XY genital ridges as early as embryonic day (E) 10.5 (25-28).…”
mentioning
confidence: 99%